Psychometrics properties of the spiritual transcendence scale (STS) among Iranian university students - Moshki, Mahdi (Journal of spirituality in mental health, 2023)
In this cross sectional study, the subjects were 390 students. The findings revealed two components of spiritual transcendence and spiritual openness and also the questions that had high factor loadings with these components are largely consistent with the findings of the scale’s authors. Construct validity and reliability were ascertained and the goodness of fit was determined for the Spiritual Transcendence Scale (KMO: 91). The ensemble of the model’s coefficients are x2/sd = 418.39, RMESEA = .68, NFI = .95, CFI = .97. Results showed that the exploratory two-factor analysis (EFA) of this research is good-fitted without the need for modification.